Graphic news : how sensational images transformed nineteenth-century journalism - Frisken, Amanda (History of communication., 2020)
""You furnish the pictures and I'll furnish the war." This famous but apocryphal quote, long attributed to newspaper magnate William Randolph Hearst, encapsulates fears of the lengths to which news companies would go to exploit visual journalism in the late nineteenth century. From 1870 to 1900, newspapers disrupted conventional reporting methods with sensationalized line drawings. A fierce hunger for profits motivated the shift to emotion-driven, visual content. But the new approach, while popular, often targeted, and further marginalized, vulnerable groups. The author examines the ways sensational images of pivotal cultural events-obscenity litigation, anti-Chinese bloodshed, the Ghost Dance, lynching, and domestic violence-changed the public's consumption of the news. Using intersectional analysis, Frisken explores how these newfound visualizations of events during episodes of social and political controversy allowed newspapers and social activists alike to communicate-or challenge-prevailing understandings of racial, class, and gender identities and cultural power"--